DIAGNOSTIC ELEMENTS AND TECHNOLOGICAL ASPECTS IN ELABORATION OF CLEAR ALIGNERS - A SYSTEMATIC REVIEW - Maria-Antonela Beldiman; Cristina (Cîșlariu); Georgeta Zegan; Gabriel Trinh Van Dam; Georgiana Macovei (Romanian Dental Association for Education, 2020)
Aim of the study In current clinical practice, the approach to appropriate orthodontic therapy should be considered by the specialist, with the evaluation of a complete clinical and radiological examination, for dental and facial diagnosis. Materials and methods. For our study, we conducted an electronic research about diagnostic elements and technological aspects for clear aligners in some databases - Web of Science, Google Scholar, PubMed, looking for significant papers and literature review. Results The aesthetic demand of patients has led research to the development of clear aligners. According to production methods, they can be grouped into two categories - aligners made from thermoplastic materials via manual set up and CAD-CAM technologies to design and produce aligners. Conclusions. The aligners represent a true orthodontic evolution, due to their aesthetics; the contribution of CAD-CAM technology allows a diagnosis and development of treatment plan easier for the practitioner and more educational for the patient.